Suppression of Virus Specific Immune Responses by IL-10 in Acute Dengue Infection - Malavige, Gathsaurie Neelika (Public Library of Science, 2013)
BACKGROUND: Elevated IL-10 has been shown to be associated with severe dengue infection (DI). We proceeded to investigate the role of IL-10 in the pathogenesis of acute DI. MATERIALS AND METHODS: Ex vivo and cultured IFNγ ELISpot assays for dengue virus (DENV) NS3 protein and non dengue viral proteins were carried out in 26 patients with acute DI (16 with dengue haemorrhagic fever) and 12 healthy dengue seropositive individuals from Sri Lanka. DENV serotype specific (SS) responses were determined by using a panel of SS peptides. RESULTS: Serum IL-10 level were significantly higher (p = 0.02) in those who did not have in vitro responses to DENV-SS peptides (mean 144.2 pg/ml) when compared to those who responded (mean 75.7 pg/ml). DENV-NS3 specific ex vivo IFNγ ELISpot responses were also significantly lower (p = 0.0001) in those who did not respond to DENV-SS peptides (mean 42 SFU/million PBMCs) when compared to those who responded to DENV-SS peptides (mean 1024 SFU/million PBMCs). Serum IL-10 levels correlated significantly (p = 0.03) and inversely (Spearmans R = −0.45) with ex vivo DENV-NS3 specific responses but not with ex vivo non DENV specific responses (Spearmans R = −014, p = 0.52). Blockage of IL-10 in vitro significantly increased (p = 0.04) the ex vivo IFNγ ELISpot DENV-NS3 specific responses but had no effect on responses to non DENV proteins. CONCLUSION: IL-10 appears to contribute to the pathogenesis of acute dengue infections by inhibiting DENV-specific T cell responses, which can be restored by blocking IL-10.